Development Strategy of Village-Owned Enterprises Jaya Makmur Village Jenggawah Sub-District Jenggawah District Jember District - Maskur, Dafid Ali; Rohim, Rohim (Jurnal Administrasi Pemerintahan Desa, 2024)
Many village governments have established BUMDES, but some have succeeded and some have failed. The purpose of this study was to determine the development strategy of BUMDES Jaya Makmur in Jenggawah Village. This research uses qualitative research methods, with interviews with several trusted sources involved in the development of BUMDES. The results of this study, namely: First; placing the best Human Resources in managing BUMDES. Second; community involvement in developing business units. Third; marketing innovation of business units, such as: cafe, restaurant. This research further explores the challenges in community involvement in developing BUMDES.